GENERAL CHARACTERISTICS OF THE CLASSES POLYPLACOPHORA AND MONOPLACOPHORA - PRIYANKA (International Journal of Multidisciplinary Research and Studies, 2020)
The classes Polyplacophora and Monoplacophora are two groups of marine mollusks with distinct characteristics. Polyplacophora, commonly known as chitons, have a dorsal shell made up of eight separate, overlapping plates, while Monoplacophora, also known as "single-plated" mollusks, have a single, cap-shaped shell. Both classes have bilateral symmetry, a muscular foot used for locomotion, and a radula for feeding. This paper provides an overview of the general characteristics of Polyplacophora and Monoplacophora, including their morphology, ecology, and phylogeny. Polyplacophora and Monoplacophora are two classes of mollusks that are not as well-known as their counterparts such as gastropods and bivalves. This paper aims to provide a comprehensive overview of the general characteristics of Polyplacophora and Monoplacophora, including their morphology, ecology, and evolutionary history. Specifically, the paper will discuss the structure and function of the shells, radula, and nervous system, as well as the ecology and distribution of these classes. Furthermore, we will explore the evolutionary relationships of Polyplacophora and Monoplacophora with other mollusk classes.